2000
DOI: 10.1046/j.1365-2141.2000.02031.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin levels in cord blood plasma and amniotic fluid in fetuses with alloimmune thrombocytopenia and healthy controls

Abstract: Summary. To extend our knowledge of the kinetics of fetal thrombopoietin (TPO), we studied TPO levels in cord blood plasma and amniotic fluid collected from 15 fetuses considered to be at risk of fetomaternal alloimmune thrombocytopenia and also from 10 healthy controls at caesarean delivery. In the plasma of all 25 fetuses and newborn infants studied, TPO was detected above the lower limit of detection (7 pg/ml) and correlated inversely with platelet counts (r 20´53, P 0´006). At term, TPO detected in amnioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
5
20
0
Order By: Relevance
“…Our study reveals that the median TPO concentration in severe FMAIT is significantly elevated which is consistent with data from Sainio et al 17 as determined in a lower number of patients. In contrast, Porcelijn and coworkers 20 could not detect differences in TPO concentrations between fetuses with FMAIT and healthy neonates or nonthrombocytopenic fetuses with HDN.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study reveals that the median TPO concentration in severe FMAIT is significantly elevated which is consistent with data from Sainio et al 17 as determined in a lower number of patients. In contrast, Porcelijn and coworkers 20 could not detect differences in TPO concentrations between fetuses with FMAIT and healthy neonates or nonthrombocytopenic fetuses with HDN.…”
Section: Discussionsupporting
confidence: 93%
“…‐26 It is an inherent problem to gain a considerable high number of normal fetal blood samples for determining reference values. Previously, fetal TPO concentrations were compared with those measured in cord blood taken at birth in preterm and term neonates or adults 17,20 , 24,25 . In this study, fetal TPO plasma concentrations are described in fetuses with normal hematopoiesis, where perinatal effects on TPO concentrations can be excluded, as mentioned by others 27 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…MGDF mRNA has also been detected in the fetal and adult bone marrow as well as in organs such as kidney and spleen. The levels of MGDF in plasma are higher in the fetus and neonate than in the adult (17,19,20). The presence of MGDF in fetal hematopoietic tissues, such as the liver and bone marrow, indicates that this cytokine is a likely physiologic regulator of fetal hematopoiesis.…”
Section: Cd34mentioning
confidence: 99%
“…For instance, it would be important to analyze corresponding data on megakaryopoietic activity when the sample is obtained. Current data on fetal Tpo concentrations are limited and obtained from fetuses who underwent cordocentesis because of Rhesus (Rh) alloimmunization, fetal alloimmune thrombocytopenia (FAITP) or prenatal diagnosis of genetic disorders (111,117,118). Sainio et al found similar Tpo concentrations in non-thrombocytopenic fetuses (n = 7; 36-37 wk of gestation) with fetomaternal incompatibility of human platelet antigens as in controls at birth.…”
Section: Thrombopoietin Concentrations In Health and Diseasementioning
confidence: 99%